The Use of Computer-Based Assessment (CBA) in Measuring Students’ Achievement Test - Haryani Haryani (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This paper is intended to discuss the result and the performance of KPN student’s achievement through Computer Based Assessment (CBA) as the media in doing the summative test. This test refers to as assessment of learning, and aims to measure the student’s performance at the end of their course and based on the syllabus or the course textbook given by the teacher. Since the English teacher is having a burden in correcting the student’s paper examination manually in giving the feedback of the test, so this CBA model is one kind of the best solution. The method used in collecting the data is by qualitative approach. The students are given 100 multiple choice questions and the time allotment in answering the questions is about 60 minutes. There are 140 students who do the test by CBA model. From the result of the test, it can be found that there are 29% students who get score in length of 85-100, 26% get score in length of 70 – 84, 21% get score in length of 60-69, 11% get score in length of 50-59, and 13% get score in length of 31– 49. By having known this test result instantly, the teacher can decide to do the remedial test in order to increase the students’ English achievement and master the English knowledge given during one semester. This remedial test by using CBA model is very helpful for teacher in knowing the student’s achievement without spending much time in doing correction.